2020
DOI: 10.1038/s41467-020-18641-z
|View full text |Cite
|
Sign up to set email alerts
|

Strain localisation and failure at twin-boundary complexions in nickel-based superalloys

Abstract: Twin boundaries (TBs) in Ni-based superalloys are vulnerable sites for failure in demanding environments, and a current lack of mechanistic understanding hampers the reliable lifetime prediction and performance optimisation of these alloys. Here we report the discovery of an unexpected γ″ precipitation mechanism at TBs that takes the responsibility for alloy failure in demanding environments. Using multiscale microstructural and mechanical characterisations (from millimetre down to atomic level) and DFT calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…High resolution backscattered electron (BSE) image (figure 4a) shows that V-shaped γ″ with one-toone correspondence formed along TBs in IN718 alloy, which is similar to our previous finding in another γ″-strengthened superalloy (Incoloy 945X) [22]. The formation of such symmetric γ″ along TBs is attributed to the extremely low free energy in forming γ″-TB-γ″ structure compared to forming other morphologies, which originates from the interplay between the crystallographic structure of γ″ and TB of Ni matrix [22]. We examined the TBs which have developed DSBs using high resolution SEM to reveal the role of the special γ″ in the initiation of DSBs and strain localization.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…High resolution backscattered electron (BSE) image (figure 4a) shows that V-shaped γ″ with one-toone correspondence formed along TBs in IN718 alloy, which is similar to our previous finding in another γ″-strengthened superalloy (Incoloy 945X) [22]. The formation of such symmetric γ″ along TBs is attributed to the extremely low free energy in forming γ″-TB-γ″ structure compared to forming other morphologies, which originates from the interplay between the crystallographic structure of γ″ and TB of Ni matrix [22]. We examined the TBs which have developed DSBs using high resolution SEM to reveal the role of the special γ″ in the initiation of DSBs and strain localization.…”
Section: Resultssupporting
confidence: 87%
“…In addition, the two TBs in figure 4c and 4d both have high Schmid factors for {111}<110> slip (0.44 and 0.45, respectively), so they are readily the easy path for dislocation activities. In addition, Zhang et al [22] found out that dislocations are activated at a much lower stress level at these weakened planes compared to that in grain interiors of Incoloy 945X, which results in severe strain localization. Similar phenomenon was also observed in the in-situ HRDIC results in figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 However, the penetration of a large amount of hydrogen and its isotopes in the fusion reactor service environment induces hydrogen embrittlement (HE) and degradation of materials, shortening the lifetime and causing safety issues. [3][4][5][6][7] It is known that the diffusion of H atoms is the leading cause of HE. [8][9][10] The use of hydrogen permeation barrier coatings that reduce the penetration of H is an effective means.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in nickel-based superalloys, prior studies by Villechaise et al and Larrouy et al theorize that areas where localized slip impinges on a neighboring grain boundary, but the slip cannot transmit into the neighboring grain, are favorable crack initiation sites due to the slip shearing the physical grain boundary [6,7]. A recent high-resolution deformation study by Stinville el al on the Inconel-718 nickel-based superalloy furthered these findings by coupling two-dimensional electron backscatter diffraction (2D-EBSD), an microscopic orientation field measurement, and heaviside digital image correlation (H-DIC), a microscopic strain field measurement, to spatially correlate the same slip impingement behavior with plumes of intense intragrain lattice rotation (up to 10 • ), termed microvolumes, as shown in Figure 1 [6][7][8][9][10][11]. These observations, when combined with the crack initiation theory above, provide microvolumes as measurable features that may indirectly identify grains with the most potential for initiating a fatigue crack.…”
Section: Introductionmentioning
confidence: 93%